Influence of the Cooling Rate on the Morphology of Spheroidic Graphite Obtained by the CO2 Process - Souza, Mauro Carlos; Araújo Santos, Antonio Carlos de; Lima Pinto, Wilma Clemente de; Avelino, Mila Rosendal (Cadernos UniFOA, 2013)
The mechanical properties of cast metallic materials are strongly influenced by processing parameters, such as percentage of silicate, sand granulometry, and metallurgical processing. The ductile iron cast produced by the CO2 process depends on variables that determine the behavior of the material in service, such as the cooling rate and chemical composition. This study evaluated the influence of the cooling rate on the spheroidic graphite. In order to determine this effect, a simulation was performed in specimens with 20, 25, and 30 mm in thickness, through the characterization of type, measurement of nodule size, and distribution of nodules. Chemical analysis and mechanical resistance tests were performed. The 25 mm thick specimen showed the best behavior among the three thicknesses evaluated, presenting the formation of many small nodules and a small amount of larger nodules in the center.